The effect of mudharabah financing on the development of MSME in the new normal era - Sari, Antin Laila; Estiningrum, Sri Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
MSMEs (Micro Small and Medium Enterprises) are known as one of the sectors which had undergone a decline in line with the COVID-19 pandemic. Capital is known to be an important issue for MSMEs at the time of the pandemic. The fluctuating income also influences the economy. The existence of Islamic financial organizations with various sharia-based financing products now becomes such a good option to be applied. One of the financing products in financing with a mudharabah contract. This study was done on purpose to help determine how the effect of mudharabah financing on the development of MSMEs in the new normal era. This research applies a quantitative approach, and the primary data to make a questionnaire to customers of MSME owners listed at Al Madani sharia cooperative. The analytical method used is the instrument test, classical assumptions, hypothesis testing and the coefficient of determination. Produces that mudharabah financing has a positive effect on the development of MSMEs. Reflected from the test result a calculated value of 5.980> 2.023 and a significance of 0.000<0.05. So, mudharabah financing gives such a positive influence on the development of MSMEs.